(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The goal is to make an analytical study of the state of innovation development and innovation obsolescence in 15 machine-building companies in the Republic of Bulgaria. On this basis, the regularity of innovation obsolescence should be established and whether it has priority over physical wear and tear. An alternative approach for choosing solutions to reduce the harmful impact of rapid innovation obsolescence is proposed.